An Analysis of the Fragmented Legal Regime Pertaining to Rehabilitation Measures for Wetlands: a South African Perspective - Bramley Jemain Lemine; Chesné Albertus; Thokozani Kanyerere (Center for Journal Management and Publication, 2022)
We are losing wetlands three times faster than forests. Many efforts have been made to ensure its protection and conservation, including rehabilitation. Rehabilitation measures have been adopted in policies of various jurisdictions. In South Africa, however, these efforts are all over in pieces of different legislation (see Table 1). Paper 1 expressed the extent of the fragmentation through a situational analysis and the effect of such fragmentation. Recommendations were made to bolster rehabilitation provisions for inclusion in South Africa’s envisaged National Joint Wetlands Policy. This paper aimed to address two issues: 1. To learn lessons by focusing on three countries’ rehabilitation provisions and their method of inclusion; and 2. designing a rehabilitation goal and policy objectives that adequately fits South Africa’s system. The findings are that a SciProfPol objectives are required for wetlands rehabilitation due to the nature of South Africa’s legal system, and the lessons by other jurisdictions may not fully apply but find relevance, along with relevant adjustments.